Intervention on Parkinson disease symptoms with optical illusion visual cues in Augmented reality software - Harpa Tanja Unnsteinsdóttir 1987- (2017)
Parkinson disease (PD) is the second most common, continuous degenerative neurological disorder that manifests itself as different motor and non-motor attributes, such as gait deficiencies and attention deficits. There is no permanent cure for PD, only symptom relief. Kinesia paradoxica naturally resides within the Parkinson patient, when stimulated, it relieves symptoms of Parkinson. This study aimed to stimulate kinesia paradoxica with visual cues in Augmented reality software (AR). Single subject ABA withdrawal design was performed on one PD patient who matched controls for the study. Subjects from a nursing home in Iceland volunteered, where the measurements took place, after an introductional letter from a physical therapist. The GAITRite electronic walkway was used for reliable measurements of Functional Ambulation Performance (FAP; a quantitative gait measure). The intervention was a software creation of AR application for use on mobile devices that filtrates the ground and portray the illusion of a staircase. Accumulated 12 measurements on the GAITRite walkway were reported in this study. Results showed that the AR visual illusion of a staircase had a reverse effect on gait performance. Limitations such as time constraints of measurements, group sensitivity and programming failure, resulted in excluded subjects, as well as lack of reliability and validity in findings. Útdráttur Parkinson sjúkdómur (PS) er næst algengasti samfelldi taugahrörnunarsjúkdómurinn, sem lýsir sér í mismunandi hreyfi- og ekki hreyfieinkennum, líkt og truflað göngulag og athyglisskerðing. Það er engin varanleg lækning við PS, einungis er hægt að halda einkennum í skefjum. Kinesia paradoxica er náttúrulegt fyrirbæri sem býr innra með Parkinson sjúklingnum, þegar það er örvað, þá léttir það á einkennum Parkinson. Þessi rannsókn miðaði að því að örva kinesia paradoxica með sjónrænum bendingum í gagnauknum veruleika hugbúnaði. Einn þátttakandi sem greindur var með PS var tekinn fyrir í einliða vendisniði, ABA. Þátttakandi af ...